MICRO-TEACHING REHEARSAL WITH DIGITAL VIDEO: ENHANCING THEIDEOLOGY OF MICRO-TEACHING EXERCISE - Okuntade Japhet Omolere; Ebimomi Oluwafemi Ebiseni; Luckay Melanie B. (Indonesian Journal of Education (INJOE), 2025)
The ideology behind micro-teaching, a widely used pedagogical approach in teacher education, is currently being scrutinized and questioned regarding its effectiveness in developing the competence of pre-service teachers. This has created a concern among experts and prompted a rethink of this strategy's purpose, process, and implementation procedures. This study examines the principles behind micro-teaching exercises to an innovative approach (Digital video) that could be combined with the traditional procedure to improve micro-teaching methodology. The study adopts the qualitative method as a source of data collection. Two focus group discussions comprising five (5) participants were used, and responses were analyzed with thematic analysis, three themes were generated for discussion which include; (1)the perception of micro-teaching exercises (2) digital video as an active form of participation, and (3)in-depth knowledge of good practices. From the themes, the findings of this study reveal how digital video and teaching rehearsals may improve the implementation procedure and methods of micro-teaching exercises to enhance the pre- service teachers' competence.